Reposisi Pendidikan Agama Kristen dalam Kebijakan Pendidikan Nasional - Malonda, Venny Grace; Olis, Olis (Sekolah Tinggi Teologi Kadesi Bogor, 2025)
Christian Religious Education plays a strategic role in shaping the character and spirituality of students as an integral part of the national education system. However, in the context of education policy in Indonesia, Christian Religious Education is often marginalised due to the dominance of secular and cognitive approaches that neglect the dimensions of values and morality. This article aims to analyse the urgency of repositioning Christian Religious Education in national education policy through a qualitative approach based on literature review. The findings indicate that Christian Religious Education not only serves as a means of transferring religious knowledge but also plays a role in building students' personalities that are inclusive, compassionate, and socially responsible. The main challenges faced by Christian Religious Education include inconsistencies between regulations and implementation in the field, a shortage of Christian Religious Education teachers with civil servant status, a curriculum that is not contextual, limited resources, and negative perceptions towards Christian education. The repositioning of Christian Religious Education proposed in this study includes six strategic steps: strengthening inclusive policies, developing a contextual curriculum, improving the quality and quantity of teachers, providing supporting facilities, integrating Christian values into the Pancasila student profile, and strengthening collaboration between churches, schools, and the government. By systematically and sustainably repositioning Christian Religious Education, it can play a more significant role in realising holistic, meaningful, and values-based national education. This repositioning is important not only for the benefit of Christians but also to enrich Indonesia's educational heritage in shaping future generations who are moral, inclusive, and have high integrity.